The current landscape of gastric cancer and gastroesophageal junction cancer diagnosis and treatment in China: a comprehensive nationwide cohort analysis - Yang Chen; Keren Jia; Yi Xie; Jiajia Yuan; Dan Liu; Lei Jiang; Haoxin Peng; Jia Zhong; Jian Li; Xiaotian Zhang; Lin Shen (Journal of Hematology & Oncology)
Abstract Background Gastric cancer is the fifth most common cancer globally and is associated with significant morbidity and mortality. Despite its alarming prevalence, limited comparative evidence exists on its treatment efficacy and prognosis across diverse China populations. Methods To address this, our study used a large-scale dataset from the National Cancer Information Database, including data from 220,304 patients from 53 leading hospitals across 27 provinces in China. Results From 2017 to 2023, early-stage (Stages I-II) gastric cancer diagnoses increased to 35.63% of all cancer cases. Our study evaluated the neoadjuvant treatment strategies, adjuvant post-operative therapy, first- and second-line management for progressive stages, alongside current gastric cancer treatment guidelines in China. Notably, immunotherapy accounted for 16.17% and 23.28% of first- and second-line treatments for late-stage gastric cancers, and 14.56% and 5.00% for neoadjuvant and adjuvant therapies, respectively. Analysis of survival rates revealed that the 1-, 2-, 3-, 4-, and 5-year survival rates were 74.07%, 54.89%, 44.21%, 37.97%, and 33.53%, respectively. The 5-year survival rates across stages I-IV were 85.07%, 49.34%, 35.56%, and 13.15%, respectively. Conclusions These findings offer critical insights into the current state of gastric cancer treatment in China and can inform future initiatives to improve therapeutic outcomes for patients with gastric cancer.